Neoadjuvant QUAD shot for downstaging or temporizing locally advanced oral cavity cancer prior to definitive surgery. (October 2022) - Nguyen, My-Lien; Hsieh, Meng-Lun; Henson, Christina; Krempl, Greg
Highlights: Modified Quad Shot radiotherapy can downgrade head and neck cancer preoperatively. Modified Quad Shot radiotherapy can temporize head and neck cancer. Prospective trials of Quad Shot radiotherapy in preoperative downgrading are needed. Abstract: Objectives: The mainstay of oral cavity cancer treatment is surgery, often with adjuvant therapies. However, patients often present with locally advanced disease and downstaging would render surgery more feasible. We evaluated hypofractionated radiation therapy (QUAD Shot) prior to definitive surgery for head and neck cancers, with a goal of downstaging. Materials and Methods: Eighteen patients with primary head and neck malignancy, predominantly locally advanced oral cavity cancers, received QUAD Shot radiation therapy from June 2016 to July 2021. External beam radiation therapy was delivered to the primary lesion in four fractions over two days, two fractions/day at least six hours apart with total dose ranging from 1400 cGy to 1500 cGy. Twelve patients proceeded to definitive surgery. Results: Of the twelve patients receiving surgery, one had complete response to radiation therapy with no pathological disease seen at surgery. Four patients had a partial response, defined as downstaging on final pathology. Five patients showed no response, and two had progressive disease defined as upstaging on final pathology. Seven patients had radiographic primary tumor shrinkage ≥ 0.5 cm following Quad Shot. The Quad Shot was tolerated well with no reported adverse effects. Conclusion: Discrepancies between clinical- and pathological-staging are common and expected. However, ∼40 % of our patients experienced downstaging following QUAD Shot. Thus, neoadjuvant radiation therapy may be viable for temporizing tumor growth while awaiting surgery, or for downstaging and thus facilitating more technically feasible and less morbid surgery for locally advanced head and neck cancers.